Intercropping of cowpeas and beets under different amounts of silk flower incorporated into the soil - Medeiros, Maria Luiza de Souza; Demartelaere, Andréa Celina Ferreira; Lima, Jailma Suerda Silva; Silva, Maiele Leandro; Pádua, Guilherme Vinicius Gonçalves (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
Aiming to provide subsidies to the research and cultivation of intercropping of cowpea with beet and fertilization with spontaneous species. The objective of this work was to determine amount of silk flower that must be incorporated in the soil with purpose of promoting the best yield of these crops. The experiment was conducted at the Rafael Fernandes Experimental Farm, located in the Alagoinha district-Rio Grande do Norte. The experimental design was a randomized complete block with 4 treatments (10, 25, 40 and 55 t ha-1 doses of silk flower fertilizers) and 5 replicates. For the weight characteristics of 100 grains, number of grains per pod, weight of fresh grains and fresh pods of cowpea consortium with beet, obtained high rates when 53 t ha-1 of silk flower were added; 46.49 t ha-1 of silk flower; 46.89 t ha-1 of silk flower and 46.98 t ha-1 of silk flower, respectively. In beet, increasing responses were found for plant height, leaf number, commercial and total productivity, and productivity classified, in the amounts of 55 t ha-1; 44.21 t ha-1; 18.59 t ha-1; 22.23 and 55 t ha-1, respectively. For the economic indicators, gross income, net income, rate of return and profitability index, were obtained: R 31,784.46; R 10,732.57; 1.54 and 35.28 %, respectively. The consortium between beet and cowpea was efficient and the best agronomic performance was obtained in the incorporation of 55 t ha-1 and 47 t ha-1 of silk flower.